Determination of Vitamin D Status in a Population of Ecuadorian Subjects. (16th August 2017) - Maldonado, G.; Paredes, C.; Guerrero, R.; Ríos, C.
Abstract : Introduction . Vitamin D is a preprohormone known to play a key role in phosphocalcic metabolism; its main source comes from the synthesis at the skin level by ultraviolet (UV) radiation. Objective . The purpose of this study was to determine the levels of vitamin D in an Ecuadorian population. Materials and Methods . Retrospective study of Ecuadorian subjects from the city of Guayaquil, who had an initial study of 25 (OH)-D serum, as the indicator of Vitamin D status, in the period of 2015-2016. Results . A total of 269 Ecuadorian subjects were analyzed, with a mean age of 54.73 ± 16.58; 85% (229) were females and 15% (41) males; mean vitamin D was 27.29 ± 10.12 ng/dl[ 6.41 –88.74 ] ; 70% of the population showed levels below 30 ng/dL of vitamin D, whereas only 30% (81) had normal values. 69% (185) had levels between 29 and 10 ng/dl and 1% (3) levels below 10 ng/dl. High levels of vitamin D were evidenced in the summer months in relation to the winter months. Conclusion . It is evident that, despite the location of Ecuador and the intensity of UV rays it receives throughout the year, Ecuadorian subjects have insufficient levels of vitamin D.